GROUNDING PROPHETIC COMMUNICATION BASED PREACHING AMONG THE STUDENTS OF RUMAH TAHSIN AN NAHL - Mariyam, Siti; Triyaningsih, Heny; Hasanah, Uswatun; Humaidy, Mohammad Ali Al; Amatillah, Zulfa; Ani, Ani (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
This community service activity aims to improve the understanding and skills of the students of Rumah Tahsin An Nahl in presenting down-to-earth and impactful preaching in the wider community. The implementation method in this community service activity uses the PAR (Participatory Action Research) method, which actively involves all relevant parties or stakeholders to study ongoing actions to make better changes. This activity was carried out at the Rumah Tahsin An Nahl in RT 01, RW 02, Pangloros, Tlanakan, Pamekasan. There were 25 participants on July 30, 2024. The results of the service showed a significant increase in the students' understanding and interest in preaching based on prophetic communication, with understanding increasing from 45% before the program to 84% afterward, and interest increasing from 38% to 81%. This means that this program has succeeded in strengthening the students' understanding and motivation in applying prophetic communication in their preaching. Recommendations for further steps include the development of student learning materials, further training, and collaboration with other institutions to expand the reach of the Rumah Tahsain An Nahl students' preaching. Similar activities need to be continued to improve the communication skills of future preachers.